2009
DOI: 10.15288/jsad.2009.70.839
|View full text |Cite
|
Sign up to set email alerts
|

Item Response Theory Analysis of Lifetime Cannabis-Use Disorder Symptom Severity in an American Indian Community Sample

Abstract: ABSTRACT. Objective: the aim of this study was to use item Response theory to assess Diagnostic and statistical Manual of Mental Disorders, third edition, Revised (DsM-iii-R), lifetime cannabis-use disorder (cuD) symptom severity and its relationship to first cannabis use before age 15 years, male gender, and childhood conduct disorder in an american indian community sample. Method: the semi-structured assessment for the genetics of alcoholism was used to determine demographic information, age at first use, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(19 reference statements)
0
12
1
Order By: Relevance
“…This is consistent with a previous study that tested for DIF of DSM-III-R (American Psychiatric Association, 1987) cannabis abuse and dependence symptoms as a function of sex in the present Native American sample. This study reported signifi cant evidence of DIF as a function of sex for only a single symptom (hazardous use) (Gilder et al, 2009), though other studies have reported more prominent sex differences (Harford et al, 2009;Srisurapanont et al, 2012).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This is consistent with a previous study that tested for DIF of DSM-III-R (American Psychiatric Association, 1987) cannabis abuse and dependence symptoms as a function of sex in the present Native American sample. This study reported signifi cant evidence of DIF as a function of sex for only a single symptom (hazardous use) (Gilder et al, 2009), though other studies have reported more prominent sex differences (Harford et al, 2009;Srisurapanont et al, 2012).…”
Section: Discussioncontrasting
confidence: 58%
“…As part of a larger study examining the etiology of substance use disorders in a community sample of American Indians living on reservations (see Ehlers et al, 2001Ehlers et al, , 2004Ehlers et al, , 2007Gilder et al, 2004Gilder et al, , 2009), the present study applied IRT methods to accomplish two specifi c aims: (a) to evaluate whether cannabis misuse symptoms assess a continuous latent trait that indexes the severity of cannabis use in both Native Americans living on reservations and European Americans and (b) to evaluate whether individual cannabis misuse symptoms differentially index severity in these two populations. Because the Native American community under study has been shown to exhibit very high rates of substance use disorders (e.g., 70% alcohol dependent, 60% cannabis dependent), we chose to use an equally affected population of European Americans for the present report, the University of California, San Francisco (UCSF) Family Alcoholism Study population (70% alcohol dependent, 44% cannabis dependent), which is a nationwide population-based sample selected for the presence of alcohol dependence (Ehlers et al, 2010).…”
mentioning
confidence: 99%
“…The present report is part of a larger family study exploring risk factors for substance dependence in a community sample of American Indians (Ehlers et al, 2001a, 2001b, 2001c, 2001d, 2004a, 2008c; Gilder et al, 2004, 2006, 2007, 2009). The lifetime prevalence of trauma and substance dependence in this Indian population is high and genetic and environmental risk factors for substance dependence have been identified (Ehlers and Wilhelmsen, 2005, 2007; Ehlers et al, 2004b, 2006, 2007a, 2007b, 2007c, 2008a, 2008b, 2009, 2010a, 2010b, 2011, 2012; Gizer et al, 2011; Wall et al, 2003; Wilhelmsen and Ehlers, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The present report is part of a larger study exploring risk factors for substance dependence among Native American Indians (see Ehlers et al , 2001a,b,c,d; 2004a, 2008c; Gilder et al, 2004, 2006, 2007, 2009). The lifetime prevalence of substance dependence in this Indian population is high and evidence for heritability and linkage to specific chromosome locations and associations with candidate genes has been demonstrated (see Wall et al, 2003; Ehlers et al, 2004b, 2006b, 2007a,b,c, 2008a,b, 2009a,b, 2010a; Ehlers and Wilhelmsen, 2005, 2007; Wilhelmsen and Ehlers, 2005).…”
Section: Introductionmentioning
confidence: 99%